Moral Problems for Schechtman's Narrative Self-Constitution View of Personal Identity - (:unkn) unknown (My University, 2022)
Marya Schechtman explicates her account of personal identity, the narrative self-constitution view, from the point of the view of a question about defining characteristics. Ultimately, she argues that personal identity is self-authored, narrative in form, and thus linear, articulable, and realistic. In this paper I argue that two big problems with the narrative self-constitution view demonstrate its incoherence and tension with the actual experience of personal existence: its morally suspect implications for moral desert and moral responsibility through its narrowness in conditions for self-narrative. By running into these issues, Schechtman’s view of personal identity faces difficulties of ableism, disempowerment of abuse victims, and marginalization of alternative cultural conceptions of personhood. Specifically, groups of people who conceive of identity otherwise, in terms of articulability, matching reality, or linearity are excluded and their accounts with them. Though there may be a traditional appeal towards Schechtman’s narrative form as she defines it, the drawbacks cast doubt on such an account.
Keywords: moral responsibility; narrativity; personal identity; personhood; Schechtman